2014
DOI: 10.1073/pnas.1320488111
|View full text |Cite|
|
Sign up to set email alerts
|

Preparedness of Americans for the Affordable Care Act

Abstract: Significance The ultimate success of the Affordable Care Act (ACA) depends on how well the health insurance exchanges can bring the benefits of private competition to individuals in the form of lower premiums. Doing so requires that individuals, when shopping for health insurance, correctly weigh the benefits and costs of various insurance options. Our work suggests that the overall population, and even more so those most likely affected by the ACA, is not well equipped to do so. We documented low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
(24 reference statements)
3
43
0
Order By: Relevance
“…3033 An American Life Panel survey reported that approximately 30% of persons with an income at or below the federal poverty limit could correctly describe a deductible. 32 These findings, along with the results of our study, support the importance of outreach to Hispanic women and socioeconomically vulnerable populations about reductions in cost sharing for preventive care and other similar value-based changes in insurance policies. Otherwise, such strategies may paradoxically increase disparities if affluent and better-educated patients are more likely to understand and respond to them.…”
Section: Discussionsupporting
confidence: 83%
“…3033 An American Life Panel survey reported that approximately 30% of persons with an income at or below the federal poverty limit could correctly describe a deductible. 32 These findings, along with the results of our study, support the importance of outreach to Hispanic women and socioeconomically vulnerable populations about reductions in cost sharing for preventive care and other similar value-based changes in insurance policies. Otherwise, such strategies may paradoxically increase disparities if affluent and better-educated patients are more likely to understand and respond to them.…”
Section: Discussionsupporting
confidence: 83%
“…The implications of Affordable Care Act (ACA) for CKD are also substantial given the tremendous role that the nephrology community has played in piloting key ACA demonstration programs (40,41). Although the ACA has dramatically increased the number of low-income nonelderly adults eligible for insurance coverage including Medicaid (42), implementation of the ACA varies by state, which may limit its success (36,43). Public health policies implemented at the state level are likely to affect a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of ACA changes are likely to be very challenging, especially for those who live in poverty or near the poverty line and so for racial, ethnic or cultural minority people of color (Gorin, Gehlert, & Washington, 2010;Kimbrough-Melton, 2013;Sommers et al, 2012). Recent national and statewide surveys consistently found prevalent lacks of knowledge about ACA changes, especially among those who might benefit the most from them (Barcellos et al, 2014;Blewett, Lukanen, Call, & Dahlen, 2013;Sinaiko, Ross-Degnan, Soumerai, Lieu, & Galbraith, 2013). In aggregate it seems that the majority of those living in poverty are presently unprepared to effectively navigate the post-Obamacare health care system.…”
Section: Limitations and Implicationsmentioning
confidence: 99%